Grinding Aided Electrochemical Discharge Drilling (G-ECDD) of Borosilicate Glass and its Performance Evaluation. (2016) - Ladeesh, V.G.; Manu, R.
Abstract: Recent advancements made in the field of glass technology and advanced ceramics made researchers to think of developing hybrid machining techniques to process those materials efficiently and economically. Grinding aided electrochemical discharge drilling (G-ECDD) is a prominent one among such emerging techniques, which offer high degree of dimensional accuracy for producing holes in hard and brittle ceramics. In G-ECDD, a rotating diamond core drill acts as the tool which will be integrated with a normal electrochemical discharge machine setup. In this study, an attempt has been made to explore the effects of machining parameters like voltage, pulse-on time and electrolyte concentration on the material removal rate (MRR) of G-ECDD of borosilicate glass. A three level full factorial experimental design was adopted and the analysis of variance revealed that the significant factor that contributes to MRR is voltage, followed by pulse-on time and electrolyte concentration. Additional experiments have been conducted to identify the effect of duty ratio and frequency on MRR. The use of high frequency above 4 kHz at high duty ratio above 0.6 was found to produce significant cracks on workpiece even though an increase in MRR was observed with an increase in duty ratio and frequency. Three regions (rapid tool wear, uniform tool wear and accelerated tool wear region) are identified on the graph plotted with tool wear and machining time from which the uniform tool wear region was identified as the safe machining zone to obtain consistent machining performance. The microscopic images of the machined surface revealed the material removal mechanisms of G-ECDD.